Annual Development Plan 1960-61 Government of Uttar Pradesh - Planning Commission (Planning Commission, 1960)
Within the broad frame work of the St the Second Five-Year Plan of Rs.253.1 crores, which was apposed by the Planning Commission in 1956, internal adjustments were made in the year 1959 60 in order to make adequate provision for programmes requiring more funds.
Government of Uttar Pradesh Planning Department